Impact of E–Supply Chain Management on Customer Satisfaction Through Service Quality in Agricultural E-Commerce - Eni, Yuli; Chandra, Anggraini Kumala (Journal The Winners, 2023)
The research aimed to assess the impact of applying e-supply chain management (E-SCM) on service quality (SQ) and customer satisfaction (CS) in agricultural e-commerce. It was motivated by challenges in Indonesia that led to foodwaste due to lengthy supply chain, particularly evident in the horticulture category, such as vegetables. The inefficiencies along the chain resulted in substantial annual losses, ranging from IDR 213 to 551 trillion, equivalent to 4% - 5% of Indonesian GDP. Using associative investigation with three variables and 446 samples selected through simple random sampling, the research aimed to evaluate and enhance E-SCM performance in supply chain. The effective applicationof E-SCM offered benefits, including time and cost efficiency, work flexibility, and other conveniences. Not only this did benefit the company but also enhanced service quality and customer satisfaction. SEM-PLS was used with a reflective method, and data processing was facilitated by SMART-PLS 4 software. The results show a significant influence ofE-SCM application on service quality and customer satisfaction. Furthermore, service quality has a significant and direct impact on customer satisfaction. E-SCM influences customer satisfaction through both direct and indirect pathways, which are mediated by service quality variables.